A Case Study of Cyclic Top Coal Weakening Process Based on Highly Tough Coal Seam with Partings - Zhaopeng Wu; Junhui Wang; Zhijun Wan; Jingyi Cheng; Luchang Xiong; Lizhu Zhao; Xiaogang Liu (Shock and Vibration)
The top coal weakening process is an effective mean to increase the coal output, reduce the coal resource waste, and promote the sustainable development in a mine. The conventional blast weakening process and water injection weakening process are more widely applied in fully mechanized caving mining of hard thick coal seams, but under some special complex geological conditions, no desirable performance has been achieved in top coal weakening by one weakening process alone after substantial investment in capital and equipment. In the context of highly tough top coal with partings at working face 110501 for fully mechanized top coal caving mining in Yushutian Coal Mine, effects of parting band and high toughness on top coal breaking were studied in terms of mechanism and extent, a multifunctional compound drilling field integrating blast weakening, water injection weakening, and gas extraction was purposefully designed, and a cyclic top coal weakening process for highly tough coal seams with partings was proposed. Engineering practice and performance testing show that degree of fragmentation and mobility of top coal was improved, mean top coal recovery ratio at the working face increased by about 35%, coal resource waste decreased, and potential risks of gas explosion and mine fire were eliminated, which provides reference for top coal weakening process under similarly complex engineering conditions.